2005
DOI: 10.1158/1078-0432.ccr-05-0606
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic CD24 Expression in Colorectal Cancer Independently Correlates with Shortened Patient Survival

Abstract: Purpose: CD24 is a cell adhesion molecule that has been implicated in metastatic tumor progression of various solid tumors. We aimed to clarify the expression patterns of CD24 in colorectal cancer and to correlate these to clinicopathologic variables including patient survival. Experimental Design: 147 colorectal carcinomas and two colon carcinoma cell lines were immunostained for CD24. Cytoplasmic and membranous immunoreactivity were semiquantitatively scored. Fisher's exact test, m 2 test for trends, Kaplan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
126
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 25 publications
15
126
1
4
Order By: Relevance
“…In the present study,CD24 was predominantly membranous and cytoplasmicinCRC.The findings of Tanakaet al (24) and Weichertet al (25) were consistent with our results.Some researchers focused on the alteration of CD 24 immunolocalization from membranous to cytoplasmic.Choi et al (29) investigated a large sample of ovarian tumors and linked cytoplasmic CD24 immunoreactivity to microinvasion and that the shift from apical membranous staining in normal cells to the cytoplasmic CD24 localization in carcinoma reflects the transition of epithelial cells to a more invasive phenotype which is well-known as epithelial-mesenchymal transition of tumor cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study,CD24 was predominantly membranous and cytoplasmicinCRC.The findings of Tanakaet al (24) and Weichertet al (25) were consistent with our results.Some researchers focused on the alteration of CD 24 immunolocalization from membranous to cytoplasmic.Choi et al (29) investigated a large sample of ovarian tumors and linked cytoplasmic CD24 immunoreactivity to microinvasion and that the shift from apical membranous staining in normal cells to the cytoplasmic CD24 localization in carcinoma reflects the transition of epithelial cells to a more invasive phenotype which is well-known as epithelial-mesenchymal transition of tumor cells.…”
Section: Discussionsupporting
confidence: 93%
“…The present results showed that enhanced CD24 expression in CRC was significantly correlated with aggressive clinicopathological features.A significant increase in CD24 expression was detected with higher tumor stage, nodal metastasis and LVSI.Weichert et al (25) reported that cytoplasmic CD24 immunoreactivity was significantly associated with higher tumor stages (Dukes and pT), nodal or systemic metastasis, tumor grade and poor survival.Choi et al (26) reported that CD24 cytoplasmic expression was positively correlated with higher tumor grade, advanced stage and large tumor size.Choi et al (27) observed a significant association between CD24 overexpression and tumor grade in CRC only, but they have not seen any positive correlation between CD24 expression and nodal status and patient survival.…”
Section: Discussionmentioning
confidence: 96%
“…CD44 expression is found to predict a worsened OS (13), as is CD24 (14). However, another group found no relation between the expression of any of these markers and survival after colon cancer treatment, whilst they did conclude CD133 and CD24 to be correlated with invasiveness and differentiation (28).…”
Section: Discussionmentioning
confidence: 99%
“…CD24 is a heavily glycosylated cell surface protein, thought to have various functions in proliferation and cell adhesion (12). In colorectal cancer patients, CD44 and CD24 have been associated with decreased OS (13,14), whilst a metaanalysis showed that CD133 is correlated with a worsened OS and DFS (15). Studies regarding the expression of these markers in colonic liver metastases and its influence on survival after hepatectomy are sparse (16)(17)(18).…”
mentioning
confidence: 99%
“…CD24 is a glycoprotein preferentially expressed by B-lymphocytes, that positively regulates the proliferation of activated T-cells, and it is also described in the central nervous system. Several studies conducted on colorectal cancer demonstrated that this molecule is associated with a poor prognosis and more aggressive phenotype of tumour cells (11). ABCG2 causes decreased drug concentration within the cells by pumping chemotherapeutic drugs out of the cell (12).…”
mentioning
confidence: 99%